Between trees & waves : Internationale beeldententoonstelling Avegoor '97. - Kafka, Franz; Louppen-Laurant, J.; Rood, Kees; Stötzer, Andrea; Ulrich, Niek; Wechgelaar, Lex; Landgoed Avegoor, Ellecom (Rheden : Stichting Between Trees & Waves, 1997)
Droste, Monica ; Rombouts, Guy ; de Groen, Marjolein ; Lanters, Carel ; Pietrusky, Siegfried ; Bierman, Kees ; Limburg, Ype ; Makkink, Herman ; Stötzer, Andrea ; Wechgelaar, Lex ; Temme, Wolfgang ; Hali, Gerard ; Symons, Jerome ; Partoll, Edwin ; Tarnow, Christopher ; Dilworth, Norman ; Grüner, Christopher ; Lambertz, Ralph ; Terwindt, Eugène
korte biog. per kunstenaar p. 46-48
Nederlands
Between trees & waves : Internationale beeldententoonstelling Avegoor '97, Landgoed Avegoor, Ellecom, 5 juli tm 30 september 1997
boek